The Effect of Price Perception and Product Quality on Purchase Decisions through Asus Laptop Brand Trust in Meteor PC Bekasi Store - Rahayu Lestari; Fujiati Afriliani (Budapest International Research and Critics University, 2022)
This study aims to analyze the influence of price perception and product quality on purchasing decisions through the Asus Laptop brand trust at the Meteor PC Bekasi Store. The study source and data used primary data in the form of questionnaires, the study data was given to 96 respondents. Research sampling uses purposive sampling. The analysis method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. The results of the study partially found that price perception has a positive and significant effect on brand trust, product quality has a positive and significant effect on brand trust, and Price perception has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, brand trust has a positive and significant effect on purchasing decisions.